Konseling anak perspektif Gestalt dan Islam - Angelina, Putri Ria; Solehuddin, M; Yustiana, Yusi Riksa (LPPM Universitas Ibn Khaldun, Bogor, 2024)
This study aims to compare the effectiveness of Gestalt counseling and Islamic therapy in supporting the development of elementary school-aged children. Gestalt counseling emphasizes